A greater decline in female facial attractiveness during middle age reflects women’s loss of reproductive value - Maestripieri, Dario; Klimczuk, Amanda; Traficonte, Daniel; Wilson, Claire (Frontiers in Psychology, 2014)
Facial attractiveness represents an important component of an individual’s overall attractiveness as a potential mating partner. Perceptions of facial attractiveness are expected to vary with age-related changes in health, reproductive value, and power. In this study, we investigated perceptions of facial attractiveness, power, and personality in two groups of women of pre- and post-menopausal ages (35–50 years and 51–65 years, respectively) and two corresponding groups of men. We tested three hypotheses: (1) that perceived facial attractiveness would be lower for older than for younger men and women; (2) that the age-related reduction in facial attractiveness would be greater for women than for men; and (3) that for men, there would be a larger increase in perceived power at older ages. Eighty facial stimuli were rated by 60 (30 male, 30 female) middle-aged women and men using online surveys. Our three main hypotheses were supported by the data. Consistent with sex differences in mating strategies, the greater age-related decline in female facial attractiveness was driven by male respondents, while the greater age-related increase in male perceived power was driven by female respondents. In addition, we found evidence that some personality ratings were correlated with perceived attractiveness and power ratings. The results of this study are consistent with evolutionary theory and with previous research showing that faces can provide important information about characteristics that men and women value in a potential mating partner such as their health, reproductive value, and power or possession of resources.